The Midnight Brigade - Borba, Adam (Little, Brown and Company, 2022)
Carl Chesterfield's life is turned upside down when he realizes something is damaging bridges all over his hometown of Pittsburgh, Pennsylvania. When he finds a flyer about a mysterious monster-seeking group called the Midnight Brigade, Carl begins to investigate. He soon meets Frank, a giant troll tasked with protecting the city's bridges. And with the help of Frank and two new friends, Carl sets out to protect the city.